Omissão do café da manhã e fatores de risco cardiometabólicos em adolescentes - Souza, Marielly Rodrigues de (2020)
Breakfast is considered the most important meal of the day as it contributes to the overall health and quality of the diet. Regular consumption of this meal in adolescence is associated with nutritional adequacy, bone and cardiometabolic health. On the other hand, skipping breakfast is an unhealthy habit that has grown in adolescents and has been linked to the presence of cardiometabolic risk factors such as changes in glucose levels, insulin resistance, dyslipidemia and obesity. This study aimed to evaluate the prevalence of breakfast skipping in adolescents and its association with cardiometabolic risk factors. This work consists of two manuscripts. The first aimed to perform a systematic literature review on the association between skipping breakfast and cardiometabolic risk factors in adolescents. We included 43 articles that met the inclusion criteria. The prevalence of skipping breakfast ranged from 0.7% to 94% with a mean of 27.1% and a 95% Confidence Interval (95% CI) of 21.4; 33.0%. Skipping breakfast was associated with overweight / obesity, deleterious changes in lipid profile and high blood pressure. In addition, the definitions of this meal and the cutoff points used to classify the omission were heterogeneous and could influence the observed results. The second manuscript aimed to estimate the prevalence of skipping breakfast and to analyze its association with cardiometabolic risk factors in Brazilian adolescents. A nationally representative sample of 36,956 adolescents aged 10 to 17 years was evaluated. The prevalence of skipping breakfast was 68.7% [95% CI = 66.4; 70.8] and was associated with overweight (ORaj = 1.51), central obesity both by waist circumference (ORaj = 1.36) and waist / height ratio (ORaj = 1.44), high blood glucose (ORaj = 1.54), high insulin (ORaj = 1.45) and high glycated hemoglobin (ORaj = 1.23). Thus, skipping breakfast in adolescence is associated with the presence of cardiometabolic risk factors and the need to standardize the definition of skipping breakfast in studies is highlighted.